Inpatient Treatment for the Middle-aged and Elderly in Central China - Jiang, Yan; Wang, Yu; Li, Yang; Zhang, Yuming; Zhao, Yinjun; Wang, Xiaojun; Ma, Chi; Ma, Shuangge (Frontiers in Public Health, 2017)
Background Compared to outpatient treatment and self-treatment, inpatient treatment corresponds to more severe illness and poses more serious health and financial burden to patients. The goal of this study is to provide an updated and comprehensive description of the prevalence, characteristics, and cost of inpatient treatment for the middle-aged and elderly in central China, which is highly-populated, less-developed, and agriculture-dominating. Methods A survey was conducted in August 2013 in the Henan province. Data on 1,464 subjects were collected. Results Among the surveyed subjects, 582 had at least one episode of inpatient treatment. Subjects with different inpatient treatment status differ in the distributions of age, education, occupation, area, health insurance coverage, physical condition, and presence of chronic disease. The surveyed subjects had up to six inpatient treatments within twelve months. Different episodes have different characteristics. Age and the presence of chronic disease are significantly associated with the number of inpatient treatments. The utilization of grade III hospital for inpatient treatment is associated with gender, marital status and per capita income. The total and OOP (out-of-pocket) costs are associated with education, utilization of type III hospital and insurance utilization. Conclusions This study has provided a comprehensive description of inpatient treatment for central China, an area with low developmental and economic status. The observations may assist improving health conditions and disease treatment for this less advantaged area.